2021
DOI: 10.3389/fcell.2021.716462
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Non-coding RNAs and Angiogenesis in Glioblastoma

Abstract: One of the significant hallmarks of cancer is angiogenesis. It has a crucial function in tumor development and metastasis. Thus, angiogenesis has become one of the most exciting targets for drug development in cancer treatment. Here we discuss the regulatory effects on angiogenesis in glioblastoma (GBM) of non-coding RNAs (ncRNAs), including long ncRNA (lncRNA), microRNA (miRNA), and circular RNA (circRNA). These ncRNAs may function in trans or cis forms and modify gene transcription by various mechanisms, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 146 publications
0
29
0
1
Order By: Relevance
“…Non-coding RNAs, including microRNA (miRNA), long-chain non-coding RNA (lncRNA), small interference RNA (siRNA), and circular RNA (circRNA) are known to make up more than 75% of the genome transcripts and regulate various physiological processes during development and tumorigenesis 7 , 8 . These regulatory functions are brought about through the interaction of these non-coding RNAs with several other signaling pathways 9 , 10 . In the past decade, convincing evidence has accumulated in regards to the roles of non-coding RNAs, in particular circRNAs, in a wide range of physiological processes, as well as the pathogenesis of various diseases including cancer 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Non-coding RNAs, including microRNA (miRNA), long-chain non-coding RNA (lncRNA), small interference RNA (siRNA), and circular RNA (circRNA) are known to make up more than 75% of the genome transcripts and regulate various physiological processes during development and tumorigenesis 7 , 8 . These regulatory functions are brought about through the interaction of these non-coding RNAs with several other signaling pathways 9 , 10 . In the past decade, convincing evidence has accumulated in regards to the roles of non-coding RNAs, in particular circRNAs, in a wide range of physiological processes, as well as the pathogenesis of various diseases including cancer 11 .…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs regulating angiogenesis in cancers have been dubbed angiomiRNAs [ 85 , 86 ]. Several angiomiRNAs have been identified in glioblastomas [ 87 ], with some originating from glioblastoma-derived EVs [ 88 ]. However, studies indicating the relationship between angiomiRNAs and the EMT process in glioblastomas are limited.…”
Section: Mirna-emt-related Angiogenesismentioning
confidence: 99%
“…Tumor cells are capable of promoting angiogenesis or even differentiating into endothelial cells to form new vessels ( Pezzella et al, 2015 ; Wang et al, 2020b ). Recent advances reported that many lncRNAs are involved in mediating the abnormal angiogenesis of GBM ( Balandeh et al, 2021 ). For instance, Jia et al (2016) characterized that H19 promotes glioma-associated endothelial cell (GEC) growth and the formation of the tube through sponging miR-29a, thereby promoting angiogenic factor VASH2 expression and angiogenesis.…”
Section: Significance Of Lncrnas In Gbm Malignant Phenotypesmentioning
confidence: 99%